A Step Toward Optimizing Regenerative Medicine Principle to Combat COVID-19 - Sharma, Shilpa; Jeyaraman, Madhan; Muthu, Sathish; Anudeep, Talagavadi Channaiah; Jeyaraman, Naveen; Shringeri, Ajay Satish; Kumar, Vinodh; Somasundaram, Rajeswari; Jain, Rashmi; Jha, Saurabh Kumar (Annals of the National Academy of Medical Sciences (India), 2021)
Drugs are currently not licensed in specific to pulverize COVID-19. On an emergency basis, vaccines were approved to prevent the further spread of COVID-19. This serves as a potential background for considering the optimization of biologics. In this context, evidence on convalescent plasma and stem cells has shown a beneficial role. Here, we have considered this as plausible therapy, and further hypothesize that their cocktails will synergistically boost the immunogenicity to relegate COVID-19. This warrants a large volume clinical trial on an emergent basis, because the sooner we establish a safe and effective cure, the better.
Keywords: COVID-19; mesenchymal stem cells; convalescent plasma; pandemic